Project management for facility constructions a guide for engineers and architects - De Marco, Alberto (Springer, 2011)
This book describes concepts, methods and practical techniques for managing projects to develop constructed facilities in the fields of oil & gas, power, infrastructure, architecture and the commercial building industries. It is addressed to a broad range of professionals willing to improve their management skills and designed to help newcomers to the engineering and construction industry understand how to apply project management to field practice. Also, it makes project management disciplines accessible to experts in technical areas of engineering and construction. In education, this text is suitable for undergraduate and graduate classes in architecture, engineering and construction management, as well as for specialist and professional courses in project management.